PERFORMANCES OF THE KARAKALPAK STATE THEATER OF YOUNG AUDIENCES: RESEARCH AND RESULTS - Nag‘metov Nokisbay Asembaevich (Western European Studies, 2025)
In this article, the organization of the theater of young viewers in the Republic of Karakalpakstan. It talks about the difficulties during the formation period and about the first staged performances
Keywords: aesthetic pleasure; theater